POLA KONSUMSI HEDONISME GENERASI MILLENIAL MUSLIM TERHADAP TEORI KONSUMSI DALAM PRESPEKTIF EKONOMI ISLAM - Thoyibah, Muthiatu; Fasa, Muhammad Iqbal; Suharto, Suharto (Jurnal Ilmiah Pendidikan dan Keislaman, 2021)
Islamic consumption theory has the most basic purpose of an economy, which is to take blessings and benefits to it. In this study, it aims to find out how the application of consumption patterns among Muslim millennials, whether it has been in accordance with islamic economic consumption patterns. Of course, this research will be useful for stakeholders as an improvement material or proposal to implement islamic economics in their daily lives. Authors use this type of descriptive research and use literature studies, which is an effort to get the necessary materials by reading books and relevant scientific works, including writing published in various print and electronic media. The results show that millennials today are more concerned with the trends they see in social media, one of which is the TikTok application, especially the growing fashion trend. It changes the consumption patterns of millennials not only trying to meet their needs (need) but also force themselves to meet what they want (wants). So the Muslim millennial generation should apply Islamic consumption patterns in their lives. The application of islamic consumption theory includes ethics and principles in accordance with the Qur’an and Hadith